CO-sensing Properties of Potentiometric Gas Sensors Using an Anion-conducting Polymer Electrolyte and Au-loaded Metal Oxide Electrodes. (1st June 2015) - Goto, Toshiyuki; Hyodo, Takeo; Ueda, Taro; Kamada, Kai; Kaneyasu, Kazunari; Shimizu, Yasuhiro
Abstract: CO-sensing properties of potentiometric gas sensors using an anion-conducting polymer (ACP) as an electrolyte and metal oxides loaded with and without Au as electrodes (EC(MO) or EC( n Au/MO( T m)), respectively, MO: metal oxide (In2 O3, ZnO or Co3 O4 ), n : the loading amount of Au, 0.5∼2.0 wt%, T : heat-treatment temperature, m: heat-treatment atmosphere, air or H2 ) have been investigated in wet synthetic air (57%RH) at 30 °C. In addition, H2 -sensing properties of these sensors have also been investigated in the same gaseous conditions, to evaluate their CO selectivity against H2 . All of the EC(MO) sensors showed relatively small changes in electromotive force (EMF), i.e. responses, to both CO and H2, but the Au loading to In2 O3 and ZnO drastically improved the magnitude of CO response of the EC(In2 O3 ) and EC(ZnO) sensors, respectively. The EC( 2.0 Au/In2 O3 ( 400 air)) sensor showed larger CO response, faster CO response speed, excellent CO selectivity against H2 and better long-term stability than those of the EC( 2.0 Au/ZnO( 400 air)) sensor. The influence of moisture on the CO response of the EC( 2.0 Au/In2 O3 ( 400 air)) sensor was almost negligible in the humidity range of 40∼100%RH. The magnitude of CO response of the EC( 2.0 Au/In2 O3 ( 400 air)) sensor in wet synthetic air showed a good linear relationship with CO concentration, but the CO response was largely affected by the concentration of O2 . These results indicate that the EMF of the EC( 2.0 Au/In2 O3 ( 400 air)) sensor is probably determined by the mixed potential resulting from CO oxidation and O2 reduction. The heat-treatment conditions of the 2.0 wt% Au-loaded In2 O3 powder largely affected the CO-sensing properties of the EC( 2.0 Au/In2 O3 ( T m)) sensors. Among these sensors heat-treated in various conditions, the as-fabricated EC( 2.0 Au/In2 O3 ( 250 H2 )) sensor showed the most excellent CO selectivity against H2 in their concentration range of 10∼3000 ppm.